2017
DOI: 10.3390/su9061058
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Investigations of Water Balances of a Dune-Interdune Landscape during the Growing Season in the Horqin Sandy Land, Northeastern China

Abstract: Dune-interdune is the main landscape pattern of desert areas, such as the Horqin sandy land of Northeastern China. Exploring the temporal and spatial variation of the water balance is crucial for efficient vegetation restoration at the micro-landform scale. The SWMS-2D model was used to estimate the seasonal variations of the water balance including evapotranspiration, soil water storage changes, lateral flow and drainage, and to examine the effects of micro-landforms (i.e., the top, upper, down, and bottom po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Buildings that have land with a high topography are more impressive than those with a low topography. Topography, soil, climate, and vegetation are four things that need to be considered in supporting the appearance of the building [45].…”
Section: Resultsmentioning
confidence: 99%
“…Buildings that have land with a high topography are more impressive than those with a low topography. Topography, soil, climate, and vegetation are four things that need to be considered in supporting the appearance of the building [45].…”
Section: Resultsmentioning
confidence: 99%
“…The SWMS-2D model was validated for the SWC of the study area with an RMSE of about 0.02 cm 3 /cm 3 (Figure 2, Zhou et al 2017), which indicated a good model performance.…”
Section: Swc Dynamics Among Micro-landformsmentioning
confidence: 89%
“…Our study showed that when rainfall was less than 20 mm, maximum recharge depth at the toeslope position was similar to that at the top, upslope, and midslope positions; whereas in rainfalls under >20 mm, soil water recharge depth was larger at the toeslope position. This could be explained by water budget differences, with high-intensity rainfalls producing horizontal movement of soil water towards the toeslope and bottomland positions with larger plant cover and increasing the extent and depth of soil water recharge (Thomas et al 2008;Li et al 2013), and small rainfall events causing little surface runoff (Zhou et al 2017). Additionally, hydraulic properties differences controlled the infiltration characteristics and rainfall recharge depth of soil among micro-landforms (Zhai & Rahardjo 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Главной целью данной программы является создание «Великой Зеленой Стены» («Green Great Wall»), предназначенной для борьбы с опустыниванием, пыльными бурями, деградацией почв и дефицитом воды в ландшафтах [Li et al, 2017]. Исследования водного баланса в катенарных почвенных сопряжениях на территории с дюнным рельефом, покрытым караганой и тамариксом в песчаной области Северо-Восточного Китая (Horqin sandy land of Northeastern China) показали, что наименее благоприятными являются нижние части склонов дюн, эвапотранспирация с поверхности которых полностью перехватывает боковой сток, не доходящий до междюнных понижений [Zhou et al, 2017]. Исследование искусственных посадок караганы разного возраста и их влияния на плодородие песчаных почв в рассматриваемой области выявило закономерное накопление в почвах углерода органического вещества и азота (максимальное в слое 0-20 см, но распространяющееся до глубины 1 метра) по мере увеличения возраста лесонасаждений.…”
Section: научные ведомостиunclassified